ANALISIS TEKS LAGU ANAK-ANAK DAN KANDUNGAN PENDIDIKAN KARAKTER - Adhani, Agnes (Widya Warta, 2020)
This study aimed to describe: (1) grammatical aspects, (2) lexical aspects, (3) contextual, and (4) the content of character education in children's song texts. This study included a descriptive qualitative study of ten song texts namely "Bintang Kejora", "Burung Kutilang", "Dua Mata Saya", "Kebunku", "Kring Kring", "Layang-Layang", "Naik Delman Istimewa", "Naik Gunung","Naik Kereta Api", and “Pelangi". The research results show that (1) grammatical aspects include (a) reference: personal, demonstrative, and comparative, (b) substitution, (c) ellipsis, (d) conjunction, and (e) repetition, (2) lexical aspects include (a) synonymy, (b) antonymy, (c) hyponymy, (d) collocation, (3) the contextual includes the social context of beauty, excitement and rural culture, and (4) the contents of character education include (a) caring, (b) tough, (c) creative, (d) religious, and (e) polite and communicative.